DAMPAK PENERAPAN KONSEP ZERO DEFECT PADA PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DALAM PENINGKATAN KUALITAS SARANA DAN PRASARANA MADRASAH - Puput Anggraini; Siti Aimah (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the impact of the Zero Defect concept in the management of School Operational Assistance Funds (BOS) on improving the quality of madrasah facilities and infrastructure. This research is motivated by the continued discovery of various administrative and technical problems in the management of BOS Funds that affect the optimization of educational facilities. The research approach used is a qualitative case study design. The research location was determined purposively in a madrasah within the Darussalam Islamic Boarding School environment. Data collection techniques included observation, in-depth interviews, and documentation involving madrasah managers, pesantren caretakers, students, alumni, and guardians as informants. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the application of the Zero Defect concept increases the accuracy and discipline of managers in the planning, implementation, and reporting of BOS Funds, improves administrative order, and increases the readiness of madrasahs to face audits and monitoring. In addition, more targeted management of BOS Funds has a positive impact on the gradual improvement of the quality of madrasah facilities and infrastructure.